Geoscientific Analysis of Structural Collapses in the City of Juan C. Bonilla, Puebla, Mexico (2021)SES IN THE CITY OF JUAN C. BONILLA, PUEBLA, MEXICO (2021). - Ramos Aguilar, Rogelio (2024)
This paper presents a general analysis from the geosciences of structural collapses. The analysis was conducted in the crop fields of Santa María Zacatepec, in the city of Juan C. Bonilla, Mexico. The analysis implemented the Remote Sensing technique, facilitating the interpretation of band combinations and determining the geometry, geology, geomorphology and cartography of the site under study. A summary analysis of the work performed is presented, in addition to showing simulation models of the hydrological outflow and water acceleration in the runoff structural slopes, data that were used for the final mapping and graphic modeling. A geomorphological, geological, and topographical study of the site was conducted, using satellite and aerial telemetric techniques. Specialized software was also used for geodetic surveys, mapping in 2D and 3D models of the analysis area. Surveys of the site were carried out to determine the shape of the structure and identify potentially risk areas for the population near the collapse events. Orthophotos were obtained to calculate and determine the slope by distance-elevation, acceleration-height, water flow and force, which served to conclude the possible causes that led to the collapses and have sufficient technical data that were shared with the civil protection authorities.